Circulating heparin‐like anticoagulants: Case report and review of literature. Issue 3 (22nd December 2020) - Hou, Chenchen; Moffat, Karen A.; Gangji, Azim S.; Ning, Shuoyan
Abstract: We report a case of a 56‐year‐old woman with a history of idiopathic thrombocytopenic purpura (ITP) following splenectomy on mycophenolate mofetil (MMF), who developed moderate bleeding after stopping MMF. Her laboratory testing suggested the presence of an abnormal circulating heparin‐like anticoagulant with demonstrable anti‐Xa activity. She was initially treated with antifibrinolytic therapy and was subsequently started on MMF alongside intravenous immunoglobulin, which significantly improved her bleeding symptoms. The presence of abnormal circulating heparin‐like anticoagulants is a rare cause of coagulopathy. Few cases exist in the literature, with nearly all occurring in the setting of hematologic or solid‐organ malignancy. The mechanism by which these endogenous anticoagulants develop is unclear. Clinical manifestations range from mild bleeding and bruising to life‐threatening hemorrhage refractory to conventional therapy. Diagnosis of a heparin‐like anticoagulant is based on coagulation testing as well as exclusion of other exogenous anticoagulants, acquired inhibitors, and/or factor deficiencies.